Targeted Control of Chloroplast Quality to Improve Plant Acclimation: From Protein Import to Degradation - Yang, Xiaolong; Li, Yangyang; Qi, Mingfang; Liu, Yufeng; Li, Tianlai (Frontiers in Plant Science, 2019)
The chloroplast is an important energy-producing organelle acting as an environmental sensor for the plant cell. The normal turnover of the entire damaged chloroplast and its specific components is required for efficient photosynthesis and other metabolic reactions under stress conditions. Nuclear-encoded proteins must be imported into the chloroplast through different membrane transport complexes, and the orderly protein import plays an important role in plant adaptive regulation. Under adverse environmental conditions, the damaged chloroplast or its specific components need to be degraded efficiently to ensure normal cell function. In this review, we discuss the molecular mechanism of protein import and degradation in the chloroplast. Specifically, quality control of chloroplast from protein import to degradation and associated regulatory pathways are discussed to better understand how plant adapt to environmental stress by fine-tuning chloroplast homeostasis, which will benefit breeding approaches to improve crop yield.